RETRACTED ARTICLE: Long non-coding RNA NKILA weakens TNF-α-induced inflammation of MRC-5 cells by miR-21 up-regulation - Dandan Wang; Jiajie Zhang; Yan Sun; Nan Lv; Jianwei Sun (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Wang, D., Zhang, J., Sun, Y., Lv, N., & Sun, J. (2020). Long non-coding RNA NKILA weakens TNF-α-induced inflammation of MRC-5 cells by miR-21 up-regulation. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 498–505. https://doi.org/10.1080/21691401.2020.1716781Since publication, concerns were identified regarding image integrity in western blot Figures 1E, 2D, 2F, 4D, 4F, 5A, 5C. When approached for an explanation, the authors did not respond to our queries. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author has been informed.We have been informed in our decision-making by our editorial policies and the COPE guidelines.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.